Proposal for a new diagnostic-therapeutic algorithm in chronic rhinosinusitis with nasal polyps - Gelardi, Matteo; Giancaspro, Rossana; Cintoli, Giulia; Minafra, Salvatore Simone; Musto, Salvatore; Cassano, Michele (Acta Biomedica Atenei Parmensis, 2023)
Chronic rhinosinusitis with nasal polyps (CRSwNP) is a chronic inflammatory disease of the nose and the paranasal sinuses characterized by the presence of nasal polyps and persistent symptoms of nasal obstruction, anterior or posterior rhinorrhea, facial pain or pressure, and reduction or loss of smell, lasting longer than 12 weeks. Several therapeutic strategies are nowadays available to treat CRSwNP as a function of disease severity. However, a standardized therapeutic algorithm has not yet been proposed. Since CRSwNP severity can be assessed by the Clinical-Cytological Grading (CCG) and the consequent reduction in patients’ Quality of Life can be defined with the Sino Nasal Outcome Test-22 (SNOT-22), we aimed to propose a new diagnostic-therapeutic algorithm, that takes into consideration both the characteristics of the patients, including the CCG, nasal obstruction, and SNOT-22, and all the therapies available today.